The Effectiveness of Giving Information on Fe Drugs on Compliance and the Effectiveness of Adding Hemoglobin to Young Women in Central Bangka Regency - Syamsul Rizal Sinulingga; Muhamad Seto Sudirman; Nina Rahmadiliyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Young women are usually very concerned about body shape, so many eat inadequate food. As a result, young women are more prone to health problems, including anemia. Women of childbearing age tend to suffer from anemia because women experience menstrual cycles every month. Iron deficiency can reduce endurance so it can cause decreased productivity. Iron intake can be obtained through foods sourced from animal protein such as liver, fish, and meat. This research is an observational type using a survey method with a cross-sectional design for young women at the Nurul Falah Air Mesu Islamic Boarding School in March -October 2021. The pre-and post-test stages were carried out before and after being given PIO Fen using 2 treatment and control groups. Samples were taken from as many as 44 young women. The results showed that the pre-test scores were lower in the treatment group than the post-test scores. From the analysis of the paired t-test, it was obtained that the value of p = 0.024 where the value (p <0.05),. Whereas in the control group, it is known that the t count is -0.227, indicating that the pretest value is smaller than the posttest value. From the analysis of the paired t-test, it was obtained that the value of p = 0.747 where the value (p> 0.05). This study concluded that there was an average difference in giving PIO Fe to adherence, whereas without giving PIO, there was no difference, and there was a significant average difference in providing information on Fe drugs between those who were given PIO andnot given PIO in female adolescents